Robotic Autonomous Observatories: A Historical Perspective - Alberto Javier Castro-Tirado (Advances in Astronomy)
This paper presents a historical introduction to the field of Robotic Astronomy, from the point of view of a scientist working in this field for more than a decade. The author discusses the basic definitions, the differing telescope control operating systems, observatory managers, as well as a few current scientific applications.